THE EFFECT OF FERMENTED PAPAYA LEAF (Carica papaya L) IN THE FEED ON THE PHYSICAL AND ORGANOLEPTIC ACCEPTABILITY OF KAMPUNG CHICKEN MEAT (Gallus domesticus) - I W., Diarsa; Puger, A. W.; Astawa, I P. A. (Jurnal Peternakan Tropika; Vol 9 No 2 (2021): Vol. 9 No. 2 Tahun 2021; May - August, 2021)
The purpose of this research is to find out the effect of fermented papaya leaf in the feed on the kampung chicken meat quality. Completely Randomized Design was used with 4 treatments and 4 repetitions. Each repetition consist of 3 kampung chickens with about 95 - 103g body weight. The treatments applied were A: (feed without fermented papaya leaf),  B: (feed with 10% fermented papaya leaf), C: (feed with 15% papaya leaf) and D: (feed with 20% papaya leaf). The observed variables were physical meat quality (as of water content, water holding capacity, cooking loss, and pH) and organoleptic (colour, texture, smell, taste, and overall acceptability). The result showed that the use of 10 - 20% fermented papaya leaf in the feed (P>0,05) would be able to decrease  significantly the water content, but not show effect (P>0,05) on the water holding capacity, cooking loss, and pH of the chicken meat. The 10 - 20% content fermented papaya leaf in the feed increasing significanty (P<0,05) on the the colour and overall acceptability, but not effected (P>0,05) the texture, smell and the taste acceptability of the chicken meat. From the research it can be concluded that given fermented papaya leaf into the feed with amount of 15% is able to decrease cooking loss and increase the colour and overall acceptability of meat meanswhile not effected on other variables as well as holding capacity, pH, texture, smell and taste acceptability.   Key words : fermented papaya leaf, kampung chicken, physical meat quality, meat organoleptic